PENINGKATAN KEMAMPUAN LITERASI MEMBACA DAN MENULIS ANAK MELALUI METODE READING-DISCUSSING-CREATING-WRITING (RDCW) DI SDN 1 DASAN GERIA - Farisi, Rizki Al; Muhsini, Andriansyah; Azuro, Restu Aditya; Budiman, Lalu Muhammad Alan; Akbar, Fariz; Saufi, M. Riyadus; Yossefa, Allysa; Maulidia, Zavira Mardhatillah; Salsabila, Alya; Putra, Ida Ayu Ravikan Varapanna; Aryana, I Gusti Putu Muliarta (Universitas Mataram, 2025)
Literacy is a fundamental skill for elementary school students to develop critical thinking, comprehend information, and express ideas effectively. However, observations at SDN 1 Dasan Geria revealed that several third-grade students still struggled with reading and writing. This community service program aimed to enhance students’ literacy skills using the Reading-Discussing-Creating-Writing (RDCW) method. The method consisted of five stages: Read Me A Book, Reading Aloud, Smart Book Review, Creating Project-Based Works, and Writing Stories. The program utilized 1,000 high-quality reading materials, mostly children’s stories provided by the National Library of Indonesia. The results demonstrated significant improvement in students’ reading, writing, critical thinking, and creativity. Furthermore, the activities positively influenced students’ learning motivation, self-confidence, social collaboration, and character development. Thus, the RDCW method is proven to be an effective and sustainable literacy strategy that supports the implementation of the School Literacy Movement in elementary education.